2004
DOI: 10.1165/rcmb.2004-0158oc
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Is Crucial to Inducing a Profibrotic Environment in “Fibrosis-Resistant” Balb/c Mouse Lungs

Abstract: The individual susceptibility to pulmonary fibrosis (PF) remains a mystery, suggesting a role for genetic predisposition. The pathogenesis of PF involves a multitude of factors mediating crosstalk between various tissue components. Some factors, such as transforming growth factor beta, are recognized as key elements in the process, whereas the role of others, such as connective tissue growth factor (CTGF), is unclear. We investigated if Balb/c mice, known to be fibrosis resistant partly due to lack of CTGF ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 29 publications
(35 reference statements)
8
91
0
1
Order By: Relevance
“…Moreover, mice treated with the anti-CTGF antibody after bleomycin challenge displayed improved lung tissue architecture and reduced expression of type I collagen and ␣-SMA. Thus, these data are consistent with recent findings showing that, whereas CTGF overexpression is, on its own, insufficient for causing lung fibrosis in vivo, CTGF expression produces a susceptibility to lung fibrosis and enhances the fibrotic response (32,33). The findings from a very recent report, in which application of the anti-CTGF antibody reduced TGF␤-induced skin fibrosis in mice (34), also support our findings and strengthen the notion of a direct role for CTGF in fibrosis enhancement and progression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, mice treated with the anti-CTGF antibody after bleomycin challenge displayed improved lung tissue architecture and reduced expression of type I collagen and ␣-SMA. Thus, these data are consistent with recent findings showing that, whereas CTGF overexpression is, on its own, insufficient for causing lung fibrosis in vivo, CTGF expression produces a susceptibility to lung fibrosis and enhances the fibrotic response (32,33). The findings from a very recent report, in which application of the anti-CTGF antibody reduced TGF␤-induced skin fibrosis in mice (34), also support our findings and strengthen the notion of a direct role for CTGF in fibrosis enhancement and progression.…”
Section: Discussionsupporting
confidence: 92%
“…First, in a bleomycin-resistant mouse model (BALB/c), CTGF was not up-regulated in response to challenge with bleomycin (6). Moreover, Bonniaud and colleagues further demonstrated that adenovirus-based delivery of CTGF to a bleomycin-sensitive mouse strain (C57BL/6) caused a transient fibrotic response (32), but in the resistant BALB/c strain, the lung was rendered susceptible to bleomycin-induced fibrosis (33).…”
Section: Discussionmentioning
confidence: 99%
“…26 An increase in CTGF expression is believed to induce a profibrotic environment. 27 We confirmed the expression of CTGF to be induced in bleomycin-injected mice. CTGF promotes fibroblast proliferation and myofibroblast differentiation, thereby inducing ECM production and fibrosis.…”
Section: Discussionsupporting
confidence: 70%
“…22,34,35 We first instilled mice with AdV-CCL18 as described 11 and then, at the peak of CCL18 production (day 7), performed a second intratracheal instillation with either PBS (as a control) or bleomycin in a lower (0.01 U/mouse) or higher (0.03 U/mouse) dose to induce lung inflammation and fibrosis. Of note, the selected doses of bleomycin alone were found to be insufficient to achieve a plateauing effect on lung inflammation and fibrosis in preliminary experiments (data not shown).…”
mentioning
confidence: 99%